Public Disclosure of Taxpayer Information as a Measure to Improve Tax Compliance - Nakayama, Kiyoshi (International Monetary Fund, 2021)
This paper provides tax policymakers, who may be considering introducing a public disclosure system in order to improve tax compliance, possible options and issues to be taken into account in deciding and designing the system. The paper discusses disclosures in respect of both personal income tax and corporate income tax, and surveys existing systems. This paper was originally published in the Asia-Pacific Tax Bulletin. Shared by permission of IBFD.